Cardiovascular Management in Patients with Rheumatic Heart Disease in Hospitals: Case Study - Liza Rizki Amalia; Hesti Platini (Jurnal EduHealth, 2023)
Rheumatic Heart Disease (RHD) is a disease that rarely affects individuals. RHD occurs due to inflammation caused by group A streptococcal bacteria and can cause heart failure. RHD in Indonesia is still rare, and it is being discussed about how to handle it. The purpose of this case report is to describe nursing issues in people with RHD. The case is about 43-year-old woman who has been diagnosed with RHD since January 2022. She was taken to the hospital with complaints of heavy breathing, and her main complaint when she was treated was a feeling of palpitations all the time, and she was easily tired. The main nursing problem was found, namely decreased cardiac output. The interventions provided were non-pharmacological therapy in the form of providing a semi-Fowler's position, a cardiac diet, education, and collaboration in providing pharmacological therapy. After intervention for three meetings, the result was no longer feeling short of breath and increased patient and family knowledge about self-management of heart disease. This case report describes PJR patients by applying evidence-based practice, so it is hoped that it will be useful for health professionals to understand the assessment process for evaluation and especially how to treat patients with non-pharmacological therapy for nurses.